The ecology of electricity and electroreception. (12th October 2021) - England, Sam J.; Robert, Daniel
ABSTRACT: Electricity, the interaction between electrically charged objects, is widely known to be fundamental to the functioning of living systems. However, this appreciation has largely been restricted to the scale of atoms, molecules, and cells. By contrast, the role of electricity at the ecological scale has historically been largely neglected, characterised by punctuated islands of research infrequently connected to one another. Recently, however, an understanding of the ubiquity of electrical forces within the natural environment has begun to grow, along with a realisation of the multitude of ecological interactions that these forces may influence. Herein, we provide the first comprehensive collation and synthesis of research in this emerging field of electric ecology. This includes assessments of the role electricity plays in the natural ecology of predator–prey interactions, pollination, and animal dispersal, among many others, as well as the impact of anthropogenic activity on these systems. A detailed introduction to the ecology and physiology of electroreception – the biological detection of ecologically relevant electric fields – is also provided. Further to this, we suggest avenues for future research that show particular promise, most notably those investigating the recently discovered sense of aerial electroreception.